Tehnološka pismenost študentov, bodočih učiteljev, z vidika znanja, izkušenj ter ocene pomembnosti tehnologije v življenju in v procesu šolanja - Zuljan, Darjo; Valenčič Zuljan, Milena (Revija za elementarno izobraževanje, 2015)
Technological Literacy of Student-Future Teachers- from the Perspective of Knowledge, Experience and Evaluation of the Importance of Technology in Life and Education. Individual‘s participation in a technological society demands deep and critical understanding of technology and its impact on each individual, environment and society. Achieving technological literacy has become an important imperative of national policies; hence, the role of education along with adequate teachers’ training has become vital. In our research, we studied technological literacy of student teachers, their experiences with technology education in primary school, their estimation of impact of technology education in primary schools and at faculties as well as their views on the role and influence of technology in individual‘s life and in the society.
Keywords: technological literacy; primary school; students; future teachers